2009
DOI: 10.1038/jhg.2009.111
|View full text |Cite
|
Sign up to set email alerts
|

Human chitotriosidase polymorphism is associated with human longevity in Mediterranean nonagenarians and centenarians

Abstract: Human phagocyte-specific chitotriosidase (CHIT-1) is a chitinolytic enzyme associated with several diseases involving macrophage activation. Previous studies have demonstrated that a high activity of Chit could have widespread effects on atherosclerosis, cardiovascular disease and dementia. The 24-bp duplication in the CHIT-1 gene is associated with a deficiency in enzymatic activity. In this study, we attempted to assess whether CHIT-1 could be a plausible candidate gene responsible for human longevity. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 39 publications
4
10
0
1
Order By: Relevance
“…Numerous evidences report the central role of CHIT-1 in the expanding spectrum of disorders suggesting that overproduction of CHIT-1 could exert deleterious effect in many degenerative disorders [24]. This concept is also sustained by our previous findings in which we observed that genetic variation within the CHIT-1 gene was strongly associated with human longevity and with several phenotypes of healthy aging [39], and that a functional polymorphism in the CHIT-1 gene protects from NAFLD progression [40]. Alternative or "M 2 " macrophages, reproduce the Th2 response of T cells and are considered anti-inflammatory; they express an array of phagocytic receptors, anti-inflammatory cytokines and release products that promote tissue regeneration and healing.…”
Section: Discussionsupporting
confidence: 70%
“…Numerous evidences report the central role of CHIT-1 in the expanding spectrum of disorders suggesting that overproduction of CHIT-1 could exert deleterious effect in many degenerative disorders [24]. This concept is also sustained by our previous findings in which we observed that genetic variation within the CHIT-1 gene was strongly associated with human longevity and with several phenotypes of healthy aging [39], and that a functional polymorphism in the CHIT-1 gene protects from NAFLD progression [40]. Alternative or "M 2 " macrophages, reproduce the Th2 response of T cells and are considered anti-inflammatory; they express an array of phagocytic receptors, anti-inflammatory cytokines and release products that promote tissue regeneration and healing.…”
Section: Discussionsupporting
confidence: 70%
“…Several genes and their alteration contribute to disease susceptibility and outcomes especially in cases of autoimmune disorders and malignancies [7]. Investigators have tried to evaluate the role of genetic susceptibility to infectious disease also [8].…”
Section: Introductionmentioning
confidence: 99%
“…Although the null clinical significance of the dup-24 bp polymorphism in the CHIT1 gene has been established for some time now (Boot et al 1998;Canudas et al 2001;Piras et al 2007), it has not been determined if there is a clinical significance of the high frequency of homozygosity of dup-24 bp in CHIT1 in Amerindian populations. Some authors have proposed that a CHIT deficiency can increase the susceptibility to infections due to parasites containing chitin (Malaguarnera et al 2003), but this implication has to be tested in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…The biologic significance of the very high frequency of this gene polymorphism remains unexplained, which suggests it may have a selective advantage not yet completely understood (Canudas et al 2001;Lee et al 2007). In the African population, the dup-24 bp homozygous state is rare, with an estimated frequency of 2% (Malaguarnera et al 2003). In contrast, the frequency of the homozygous status is approximately 6% in Caucasians (Boot et al 1999).…”
Section: Introductionmentioning
confidence: 99%